Kenya : Request for Extension of the Stand-By Arrangement -- Press Release and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Kenya's Request for Extension of the Stand-by Arrangement (SBA). The extension is needed to provide additional time for the authorities to bring the program back on track and reach new understandings with IMF staff on policies and measures that would enable the completion of the pending reviews under the SBA for Kenya. The authorities have committed to strong corrective actions through adopting policies that will enable them to achieve program objectives and reduce near- and medium-term vulnerabilities. The IMF staff supports the authorities' request for an extension of the SBA for Kenya.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Board Discussion; CR; ISCR; Precautionary SBA; Program Objective; Kenya